MAKNA SIMBOL HEWAN DALAM PERIBAHASA ARAB DI MEDIA SOSIAL - Nida, Farwah Sofwatun (Multikultura, 2026)
It is known that proverbs have existed for a long time, but today researchers have identified many proverbs, especially those that use animal symbolism, and these proverbs are being republished on social media. This study aims to analyze the meanings and origins of these proverbs so that we can understand the context of their current use on social media. The research was conducted using a qualitative method with an in-depth semantic approach. Data were collected through social media research techniques, drawing from YouTube, Facebook, and Instagram. The findings indicate that animal symbols in Arabic proverbs contain both negative and positive elements. The use of animal symbolism in Arabic proverbs on social media is mostly intended to offer advice, while others depict human behavior in contexts such as satire, criticism, praise, and mockery.